Effect of the Combination of Acupressure and Moringa oleifera Extract Consumption on Elevating Breast Milk Production and Adequacy in Lactating Mothers - Wahidah, Nurul; Eko Ningtyas, Endah Aryati; Latifah, Leny (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Exclusive breastfeeding is highly recommended because the nutrition is suitable for babies. However, there are still many babies who do not get exclusive breastfeeding. For this reason, there is a need for innovation that can be used as an effort to increase the production and adequacy of breast milk for breastfeeding mothers with a combination of Accupresure and Moringa oleifera extract. This study aimed to prove the potential of a combination of acupressure and Moringa oleifera extract as an intervention in increasing the production and adequacy of breast milk for breastfeeding mothers.Subjects and Method: This study used quasi experiment and pretest-posttest design with control group conducted at the Kelingi IV/C Health Center, Musi Rawas Regency, from December 2022-January 2023. It consisted of an intervention group consisting of a combination of 2x4 minutes of acupressure and 650 mg of Moringa oleifera extract and a control group of counseling for breastfeeding mothers, namely 40 breastfeeding mothers with babies 0-6 months. The dependent variables were the hormone prolactin and baby's weight. The independent variable was the combination of acupressure and extra Moringa oleifera. The data were analyzed by Wilcoxon.Results: The indicator affected by the combination of acupressure and Moringa oleifera extract was an increase in milk production using the prolactin hormone indicator after intervention (Mean= 304.60; SD=131.22) than before intervention (Mean= 162.85; SD= 140.44), and this was statistically significant (p<0.001). There was an increase in the adequacy of breastfeeding using the infant's weight indicator after intervention (Mean= 5550.00; SD=1240.75) than before intervention (Mean= 5015.00; SD= 1444.87), and this was statistically significant (p=0.030).Conclusion: The combination intervention of 2x4 minutes of acupressure and 650 mg of Moringa oleifera extract for 10 days effectively increases the production and adequacy of breast milk for nursing mothers. Keywords: acupressure, Moringa oleifera, prolactin hormone, baby's weight. Correspondence: Nurul Wahidah. Applied Masters Program, Postgraduate School, Health Polytechnic, Ministry of Health, Semarang. Jl. Tirto Agung, Pedalangan, Banyumanik, Kota Semarang, 50239, Central Java, Indonesia. Email: wahidahnurul246@gmail.com.